A 20-year population-based study of all-cause and cause-specific mortality among people with concurrent HIV and psychotic disorders. (1st November 2022) - Yazdani, Kiana; Salters, Kate; Shen, Tian; Dolguikh, Katerina; Trigg, Jason; White, Randall F.; Closson, Kalysha; Nanditha, Ni Gusti Ayu; Honer, William G.; Vila-Rodriguez, Fidel; Lima, Viviane Dias; Montaner, Julio S.G.; et al.
Abstract : Objective: We aimed to characterize mortality among people with HIV (PWH) and psychotic disorders (PWH/psychosis+) vs. PWH alone (PWH/psychosis−). Method: A population-based analysis of mortality in PWH (age ≥19) in British Columbia (BC) from April 1996 to March 2017 was conducted using data from the Seek and Treat for Optimal Prevention of HIV/AIDS (STOP HIV/AIDS) study. Deaths were identified from the Vital Statistics Data (classified as HIV vs. non-HIV causes). Mortality trends across all fiscal years were examined. Cox models assessed the hazard of psychotic disorders on mortality; possible differences between schizophrenia and nonschizophrenia types of psychotic disorders were also evaluated. Results: Among 13 410 PWH included in the analysis, 1572 (11.7%) met the case definition for at least one psychotic disorder. Over the study period, 3274 deaths (PWH/psychosis−: n = 2785, PWH/psychosis+: n = 489) occurred. A decline over time in all-cause mortality and HIV-related mortality was observed in both PWH/psychosis+ and PWH/psychosis− ( P value <0.0001). A decline in non-HIV mortality was observed among PWH/psychosis− ( P value = 0.003), but not PWH/psychosis+ ( P value = 0.3). Nonschizophrenia psychotic disorders were associated with increased risk of mortality; adjusted hazard ratios with (95% confidence intervals): all-cause 1.75 (1.46–2.09), HIV-related 2.08 (1.60–2.69), non-HIV-related 1.45 (1.11–1.90). Similar associations between schizophrenia and mortality were not observed. Conclusion: People with co-occurring HIV and nonschizophrenia psychotic disorders experienced a significantly higher risk of mortality vs. PWH without any psychotic disorder. Implementing care according to syndemic models considering interactions between HIV and particularly episodic psychotic disorders could help manage mortality risk more effectively among PWH/psychosis+.